Social Inequality in the Movie Fantastic Mr. Fox - Avatara, Bintang; Karima, Festi Himatu; Kustantinah, Indri; Vatsiniaina, Andriamihaja Henintsoa (Allure Journal, 2024)
This research examined social inequality and the resulting conflicts in the movie "Fantastic Mr. Fox." The objectives were to identify and analyze the portrayal of social inequality within the film using Max Weber’s theory of social stratification. Using descriptive qualitative method, the study involved detailed analysis of the movie script to uncover these themes. The findings revealed that the farmers, representing the upper class, oppress the animal community, which symbolizes the lower class. This dynamic led to various conflicts, highlighting the struggles and resistance of the underprivileged against the powerful. Film analysis demonstrated how animated films can reflect real-world social hierarchies. In conclusion, the research provided a deeper understanding of the use of popular media to comment on societal issues and emphasizes the importance of empathy and collective action to address inequality. This study contributes to the field by showcasing the potential of animated films as tools for social commentary and education. This study highlights the capacity of animated films to serve as effective mediums for social critique, urging viewers to recognize and challenge societal inequalities. The findings underscore the necessity for empathy and collective action in addressing systemic oppression